PERANCANGAN BOOKLET INFORMASI KAWASAN WISATA MANDEH DI KABUPATEN PESISIR SELATAN - PUNGKI WIBOWO Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Area Mandeh is one of the attractions that are in Pesisir Selatan regency. The existence of Area attractions Mandeh as supported by the beautiful scenery of the sea and a variety of rides such as snorkeling, banana boat, and the view is still beautiful. Area Mandeh known existence and beauty, but the lack of tourists whotravel to know the limits of Area Travel Mandeh so necessary in the form of a media information booklet to provide information about the limitations of the Tourism Area Mandeh.Booklet is one effective medium for delivering information through the Booklet easier and more interesting for the target audience. The purpose of this booklet is to provide information about the limitations of Tourism Mandeh, so that later became a media official in nature tourism area Pucak Mandeh.Methodology approach departs from the literature and using 5W + 1H to understand all the information in a problem. So the selection of media and information more effectively the message understood by the target audience.This booklet will give you visual beauty of the scenery and Tourism Mandeh path towards Mandeh Area Tourism and the travel costs that would be issued to all surrounding areas Travel Mandeh located in Pesisir Selatan regency Sematera West. This booklet is expected to contribute to the development of tourism in the South Coastal District.Keyword: Booklet, Tour, Mandeh in Pesisir Selatan District